Visual servoing for monitoring and diagnosing in farming - Le, Duc Hanh; Nguyen, Phu Hien; Pham, Viet Hoa (Journal of Technical Education Science, 2018)
This paper presents a visual feedback control algorithm for a system using in the green house to monitor and diagnose health of vegetable in a garden. Firstly by using image processing, the position of a vegetable will be positioned. Secondly by using PD controller and continuously updating the position of vegetable, the PD image based visual serving (PDIBVS) algorithm is applied to move the camera to that vegetable location helping the system to track and diagnose their health. The disease need for recognizing in this paper are yellow leaf and red dot. A webcam will be attached on the 2D mechanism, if in the webcam the center of the camera coincide with the center of the vegetable the control algorithm are effective affected. The effectiveness of the proposed method is proved by doing the experiment. In the future, the algorithm can also be applied to the garden where the size is expanded.